Secondary epithelial cyst of the iris – case report - Jamrozy-Witkowska, Agnieszka; Muzyka-Woźniak, Maria; Oficjalska-Młyńczak, Jolanta; Szelepin, Łukasz (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Authors present a case of 33 years old man who developed implantation secondary cyst of the iris, after penetrating trauma in a childhood. He was treated with cyst aspiration and endolaser photocoagulation of the cyst base. Postoperatively visual function significantly improved. No recurrence of cyst was observed. Within 6 months cataract developed with pupillary obstruction caused by irydocorneal adhesions, which required reoperation. Authors indicate that management of secondary cyst of the iris may require repeated laser or surgical treatment.